Differential inflammatory responses of the native left and right ventricle associated with donor heart preservation. Issue 17 (26th August 2021) - Lei, Ienglam; Huang, Wei; Ward, Peter A.; Pober, Jordan S.; Tellides, George; Ailawadi, Gorav; Pagani, Francis D.; Landstrom, Andrew P.; Wang, Zhong; Mortensen, Richard M.; Cascalho, Marilia; Platt, Jeffrey; et al.
Abstract: Background: Dysfunction and inflammation of hearts subjected to cold ischemic preservation may differ between left and right ventricles, suggesting distinct strategies for amelioration. Methods and Results: Explanted murine hearts subjected to cold ischemia for 0, 4, or 8 h in preservation solution were assessed for function during 60 min of warm perfusion and then analyzed for cell death and inflammation by immunohistochemistry and western blotting and total RNA sequencing. Increased cold ischemic times led to greater left ventricle (LV) dysfunction compared to right ventricle (RV). The LV experienced greater cell death assessed by TUNEL + cells and cleaved caspase‐3 expression ( n = 4). While IL‐6 protein levels were upregulated in both LV and RV, IL‐1β, TNFα, IL‐10, and MyD88 were disproportionately increased in the LV. Inflammasome components (NOD‐, LRR‐, and pyrin domain‐containing protein 3 (NLRP3), adaptor molecule apoptosis‐associated speck‐like protein containing a CARD (ASC), cleaved caspase‐1) and products (cleaved IL‐1β and gasdermin D) were also more upregulated in the LV. Pathway analysis of RNA sequencing showed increased signaling related to tumor necrosis factor, interferon, and innate immunity with ex‐vivo ischemia, but no significant differences were found between the LV and RV. Human donor hearts showed comparable inflammatory responses to cold ischemia with greater LV increases of TNFα, IL‐10, and inflammasomes ( n = 3). Conclusions: Mouse hearts subjected to cold ischemia showed time‐dependent contractile dysfunction and increased cell death, inflammatory cytokine expression and inflammasome expression that are greater in the LV than RV. However, IL‐6 protein elevations and altered transcriptional profiles were similar in both ventricles. Similar changes are observed in human hearts. Abstract : Increasing duration of murine donor heart storage with subsequent ex‐vivo perfusion using clinically utilized histidine‐tryptophan‐ketoglutarate preservation solution induced progressively higher expression of IL‐1β, MyD88, TNFα, IL‐6, MCP1, and inflammasome components. This inflammatory response was disproportionately greater in the left ventricle compared to the right ventricle. We confirm that LV contractility and relaxation were also degraded to a greater degree in the left ventricle compared to the right ventricle following progressively longer periods of preservation. Murine findings corroborated with results from human preserved donor hearts where we also observed selective upregulation of TNFα, MCP1, and inflammasome components (Nlrp3, cleaved IL‐1β‐p17) in the left ventricle compared to the right ventricle during cold preservation.